A field guide for science writers - Blum, Deborah, 1954-; Knudson, Mary; Henig, Robin Marantz (Oxford University Press, 2006)
Offers a roadmap to the area of science writing. In this edition, various chapters cover the techniques of good science writing, explanatory writing, writing under deadline, clone and stem-cell research, biology of behaviour and eugenics, mental health, human genetics, as well as making sense of conflicting studies.